JARINGAN INTELEKTUAL ULAMA RIAU: Melacak Silsilah Keilmuan Syaikh 'Abdurrahman Ya'qub - Kholil Syu'aib; Zulkifli M. Nuh (Universitas Islam Negeri Ar-Raniry, 2018)
This paper wants to present research results about the intellectual network of Shaykh 'Abdurrahman Ya'qub (1912-1970 AD./1330-1389 AH.), as a scholar who took part in the early half of the 20th century in the Indragiri region of Riau. This research uses historical approach method and content analysis technique to the existing written data. This research found that the credibility of Shaykh 'Abdurrahman Ya'qub as a scholar is inseparable from his involvement in the scholars network. It turned out that Shaykh 'Abdurrahman Ya'qub had inherited knowledge from the great scholars, among others Shaykh Sa'id Yamani (1265-1352 AH.), Shaykh Muhammad' Ali al-Maliki (1287-1368 AH.), Shaykh 'Umar Hamdan (1292-1368 AH.), Shaykh Hasan bin Muhammad al-Masysyath (1317-1399 AH.), and Shaykh Muhammad Yasin al-Fadani (1335-1410 AH.). No one doubts the credibility of their scholarity, which has had such an enormous influence on the Islamic world of its time even today. Thus, due to his involvement in the network of such great scholars, it is undoubtedly the credibility of 'Abdurrahman Ya'qub as scholars, thereby increasing the treasures of scholar in Riau in particular, and in the archipelago generally.